AESTHETIC FORM OF SEGARA KELANGON ART FASHION WORKS - Dewa Ayu Putu Leliana Sari (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
Earth is the only planet in space that has an ocean of water on its surface. The world is mostly covered by sea level. The oceans play an essential role in Earth's climate and the world's water cycle. The water cycle never stops from the atmosphere to the Earth, one of which is the ocean. The sea itself is a global water system that connected. The influence of currents in the sea causes waves. The waves crashing and rolling in the sea create inspiration in designing a dress. The method used in analyzing the aesthetics of this art fashion form is a qualitative research method. The qualitative approach aims to describe an object or problem under study. Collecting data is in the form of documentation and a literature study. Sustainable fashion in the form of free styling draping is one of the solutions to responding to the latest fashion trends. This piece of clothing is sewed 100 percent using hand stitches, with the freestyling draping technique (making clothes by draping, pleating, twisting, wrapping, sewn without cutouts, and machine stitching). This technique is one way to respond to sustainability because the work can be unstitched as a sheet of cloth and can do a new job again. Segara kelangon means the beauty of the sea's waves, the endless ocean applied by the freestyling draping technique that is not cut off. The aesthetics of this clothing include a cocktail dress intended for morning or afternoon parties. The light blue or light blue color itself symbolizes honesty and trust.